Quality Assurance and the Role of SERVICOM in Effective Service Delivery: A Case Study of Obafemi Awolowo University, Nigeria - Ajila, C.O.; Ibukun, Cleopatra O. (Advances in Social Sciences Research Journal, 2021)
The paper succinctly looks at what quality assurance is. It further examines factors militating against assurance of quality and factors responsible for improving quality assurance. The second Section of the paper addresses effective service delivery and qualities of a good service provider. The third Section looks at SERVICOM and its role in effective service delivery. Obafemi Awolowo University is used as a Case Study. The paper concludes with recommendations for the sustenance of standards in Obafemi Awolowo University.